Vanillic acid and vitamin C attenuated di-2-ethylhexyl phthalate-induced testicular toxicity in adult male rats - B Ogunlade; S C Gbotolorun; O A Adedotun; K Iteire; J Adejayi (Bioscientifica, 2022)
Di-2-ethylhexyl phthalate (DEHP) is an extensively used plasticizer which has raised some concerns about its safety on human health. This study aimed at evaluating the effects of vanillic acid (VA) and vitamin C (VC) supplementation on DEHP-induced testicular toxicity. Thirty-five adult male Wistar rats were randomly divided into 7 groups (A-G) (n = 5) receiving distilled water; 250 mg/kg bw of DEHP only; 30 mg/kg bw of VA and 250 mg/kg bw of DEHP; 30 mg/kg bw of VC and 250 mg/kg bw of DEHP; 30 mg/kg bw of DEHP plus 30 mg/kg bw of VA and 30 mg/kg bw of VC; 30 mg/kg bw of VA only; and 30 mg/kg bw of VC only, respectively. At the end of the experiment, blood was taken from the heart via cardiac puncture and stored, semen was collected from the caudal epididymis for immediate sperm analysis, while the testes were excised and preserved for histological examination and biochemical analysis. The results showed a significant decrease (P < 0.05) in body weights, sperm motility, sperm volume, sperm viability and count, antioxidant levels, and reproductive hormonal levels, with a significant increase (P < 0.05) in sperm morphological defect and lipid peroxidation level in DEHP-only group compared with the control but was ameliorated after VA and VC administration compared to the DEHP-only treated animals. VA and VC supplementation attenuated the toxic effects of DEHP on the testicular functions, morphology, and semen characterization of the experimental adult male Wistar rats.